2015 IEEE Wireless Communications and Networking Conference (WCNC) 2015
DOI: 10.1109/wcnc.2015.7127711
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the resiliency of cellular base station deployments

Abstract: The National Public Safety Telecommunications Council (NPSTC) has defined resiliency as the ability of a network to withstand the loss of assets and to recover quickly from such losses. How to measure the resiliency of a base station deployment is an important consideration for network planners and operators. In this paper, we propose a resiliency measurement method in conjunction with a performance metric such as coverage or supported throughput, where we define the resiliency as the maximum number of sites t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…When it comes to the analyzing the resilience of a network, the closest studies to ours are [26], [46]. Yan et al [46] propose the metric Tower Outage Impact Predictor (TOIP) to quantify the impact of a failure of a cell tower on the number of served cellular users.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to the analyzing the resilience of a network, the closest studies to ours are [26], [46]. Yan et al [46] propose the metric Tower Outage Impact Predictor (TOIP) to quantify the impact of a failure of a cell tower on the number of served cellular users.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, our focus is also on the potential resilience improvement due to infrastructure sharing among MNOs in the same country. Contrary to [26], our work investigates both coverage as service quality as metrics, and combines models with several data sources to assess resilience.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical specifications of a 5G resilient networks have not yet been standardized but such networks are needed to provide a high level of reliability and resilience to failures to guarantee the availability to the customers such as common public and public safety responders when needed. One of the works in the recent literature has investigated the resiliency of cellular BS deployment through a measurement method in conjunction with a performance metric such as coverage or supported throughput.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that by incorporating fault tolerance mechanisms in UMTS networks can achieve substantial gains in network reliability. In LTE/EPC networks, a major concern was dedicated to the resiliency of base stations [5] [6]. The 3GPP technical specification [7] proposes some basic restoration mechanisms for gateway failures.…”
Section: Related Workmentioning
confidence: 99%